Kritik Sosial Pada Iklan Minuman Marjan Perspektif Dakwah Komodifikasi Nilai Agama - Lestari, Puji; Rubawati, Eva (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
beverage products that we can see with a variety of different stories each year and are always present at major Islamic moments such as Ramadan and Eid al-Fitr. From the story that was created, this became one of the attractions for consumers. This Marjan drink advertisement always presents folklore in Indonesia. So that the products displayed by the media through these stories have the ability to change people's behavior through words, pictures, writing, expressions, behavior that is packaged in such a way as to make it interesting. However, there is a slight difference shown in the advertisement for the Marjan syrup version of the story of Singabarong and Kelana in conveying the message. The contents of the story shown in the advertisement seem to contain elements of violence and crime that cannot be separated from these children, giving rise to social criticism which is considered to be contrary to religious values ​​and how the commodification of religious values ​​occurs in the advertisement. In this thesis, researchers use a qualitative descriptive method. This descriptive method is intended to explore and clarify a phenomenon or social reality, by describing a number of variables with Rolland Barthes' semiotic theory to find the meaning of denotation, connotation, and myth in the advertisement for Marjan syrup, the Singabarong and Kelana Story Version. From the results of this study, the advertisement for Marjan syrup, the Singabarong and Kelana Story Version, presents social criticisms when viewed from a da'wah perspective, starting from the visualizations shown such as the use of tattoos, nakedness, high-level chanting, scenes of violence and crime, and visualization of physical forms. which are exaggerated so that this can trigger audiences to justify, encourage bad behavior and contain the commodification of religious values ​​into exchange rates in the market.